Análise de desempenho baseada em lógica linear e workflow net para escalonamento de sistemas de workflow - Bruno, Lorena Rodrigues (2023)
The model of a Workflow Management System should describe the time constraints of resources over the activities of the corresponding business process. In general, typical temporal phenomena include activity execution delays, limits to the occurrence of valid intervals over the activities, limits to valid intervals over resources (limit to resources life cycle), limits to duration of process execution, time distance between two activities, etc. In this study, a Workflow net model incremented with time intervals to describe the duration of activities and waiting times is presented. To define the execution of activities minimum and maximum intervals, a time constraint propagation mechanism based on the sequent calculus of Linear Logic and on symbolic dates is proposed. Using Colored Petri nets, it is possible to separate the process model from the resource model and formally define the communication mechanisms between the two models. Each token from the Colored Petri net will then be able to carry the time information of each case, such as the start and end time of each activity the case will have to perform to complete the Workflow process. Such temporal data can be represented as a set of colors from the CPN model and will be used to monitor the execution of the process in order to find the right amount of resources and the best scheduling technique involved in the execution of activities. The simulation of the CPN with time information then allows estimating the percentage of cases that respect the time constraints of the process (deadline delivery dates), in addition with improving resource planning in Workflow Management System.